Analysis on Effects of Process Parameters CNC Flame Cutting on Dimensional Inaccuracy Using Taguchi Method and ANOVA - Prasetya, Reihan Rafly; Tranggono (Journal Knowledge Industrial Engineering (JKIE), 2025)
Carbon steel is a primary material in various engineering applications that require cutting accuracy to maintain product quality. Advances in flame cutting technology in the manufacturing industry highlight the importance of understanding proper parameter settings. Incorrect parameter adjustments can lead to inaccuracy, material defects, and increased operational costs. In this study, the Taguchi method combined with ANOVA will be used to optimize dimensional inaccuracy in the CNC flame cutting process on SS400 steel plates. The effects of variations in cutting parameters, including cutting speed, gas pressure, and oxygen pressure, on the dimensional inaccuracy of the cut were identified. The analysis results show that gas pressure is the most influential parameter, with a contribution of 86.31%, followed by cutting speed at 6.06% and oxygen pressure at 2.42%. The optimal parameter combination for minimizing dimensional inaccuracy was found at a cutting speed of 319 mm/min, gas pressure of 4 bar, and oxygen pressure of 6 bar. These findings highlight the importance of adjusting gas pressure to improve cutting accuracy and reduce operational costs and time at PT XYZ.